Evaluating student management program effectiveness using CIPP model and glickman quadrant: a quantitative study - I Nengah Sudarsana; Dewa Gede Hendra Divayana; Basilius Redan Werang (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
Evaluating student affairs programs remains a persistent challenge in many developing-country education systems, where strong policy intentions often collide with limited resources. This study examines the effectiveness of a student management program at SMP Negeri 1 Kuta Utara using the Context–Input–Process–Product (CIPP) evaluation model, with particular attention to how resource constraints shape overall program performance. Employing an evaluative quantitative design, data were collected from 104 purposively selected stakeholders through questionnaires, structured observations, and document analysis, and analyzed using the Glickman Quadrant. The evaluation reveals a (+ - + +) pattern, indicating that while the program is overall effective and feasible to continue, its effectiveness is structurally constrained by a negative input component. Specifically, inadequate operational funding, insufficient supporting facilities, and an imbalance between the number of student supervisors and students limit program scalability and long-term sustainability. Despite these constraints, positive context alignment, disciplined and well-coordinated implementation processes, and favorable product outcomes such as improved student discipline, enhanced non-academic achievement, and strengthened character development demonstrate the program’s resilience. The study contributes empirical evidence that process quality can partially compensate for weak inputs, but not without risk to sustainability. Practically, the findings recommend targeted investment in student affairs resources, supervisor capacity building, and facility enhancement to prevent erosion of program gains. Theoretically, this study underscores the diagnostic value of the CIPP Glickman integration for identifying hidden structural weaknesses in otherwise “effective” educational programs.